2016
DOI: 10.1111/aji.12551
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐mullerian hormone levels decline with the presence of antiphospholipid antibodies

Abstract: APAs but no other immune markers appear associated with decreased levels of AMH, supporting the hypothesis that non-specific autoimmunity may adversely affect ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…10 A 2014 study assessed the ovarian reserve of patients with APS and observed that these women had a lower count of antral follicles than those in the control group. Vega et al, in 2016, 29 demonstrated a strong association between aPL positivity and decreasing levels of antimullerian hormone. Thus, antiphospholipid antibodies may represent the 1 st laboratory markers for early ovarian failure associated with autoimmunity.…”
Section: Antiphospholipid Antibody Syndrome and Primary Infertilitymentioning
confidence: 97%
See 2 more Smart Citations
“…10 A 2014 study assessed the ovarian reserve of patients with APS and observed that these women had a lower count of antral follicles than those in the control group. Vega et al, in 2016, 29 demonstrated a strong association between aPL positivity and decreasing levels of antimullerian hormone. Thus, antiphospholipid antibodies may represent the 1 st laboratory markers for early ovarian failure associated with autoimmunity.…”
Section: Antiphospholipid Antibody Syndrome and Primary Infertilitymentioning
confidence: 97%
“…It also can decrease ovarian reserve. 29 The term ovarian reserve, traditionally, has been used to describe the reproductive potential of a woman; in other words, the quantity and quality of the oocytes she possesses. However, ovarian reserve markers serve as a substitute for oocyte quantity, but are poor indicators of oocyte quality.…”
Section: Antiphospholipid Antibody Syndrome and Primary Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 The presence of aPL could be associated with a lower ovarian reserve. 41 The ANA, on the other hand, could impact the embryo development as the development of murine embryos is blocked while incubating with ANA. 42 A recent systematic review shows that the presence of ANA could be correlated to poorer IVF outcomes.…”
Section: Prevalence Of Autoantibodies In Endometriosisassociated Inmentioning
confidence: 99%
“…For females, the etiologies can be divided by organs into ovulation disorders [polycystic ovary syndrome (PCOS), premature ovarian insufficiency (POI), etc. ], tubal (Vega et al, 2016).…”
Section: Serum Autoantibodies and Female Infertilitymentioning
confidence: 99%